Neighborhood perceptions and parent outcomes in family based prevention programs for thai adolescents: The role of program engagement - Hilary F. Byrnes (2018)
Due to concerns over Thai adolescent risky behaviors, effective prevention strategies are needed. Determining the role neighborhood context plays in program engagement and outcomes may inform these strategies. This study includes 170 mother-adolescent pairs (M = 13.44, SD = .52) in Bangkok, Thailand in a prevention program for adolescent substance use and sexual risk. Neighborhoods were related to engagement, which was critical to outcomes. Neighborhood disorganization was related to confidence in program effects and program completion. Completion was related to increased ATOD communication. Neighborhood cohesion was related to less program enjoyment, while neighborhood social control was related to more enjoyment. Enjoyment was related to increased ATOD communication and formation and monitoring of alcohol rules. Prevention strategies should focus on neighborhood contexts and enhancing engagement. © 2011, Baywood Publishing Co., Inc.